Effect of surface kinetics on the step coverage during chemical vapor deposition - Hwang, GS; Moon, SH; Nam, SW; Shin, CB (MATERIALS RESEARCH SOCIETY, 1999)
Profile evolution simulations during chemical vapor deposition based on a 2D continuum model reveal that the type of surface kinetics plays an important role in determining step coverage of films deposited in high aspect ratio trenches and vias. Linear surface kinetics, resulting from an adsorption rate limited process, is found to cause difficulty in bringing about conformal step coverage in deep narrow trenches without reducing the growth rate considerably, Under such condition, void-free filling cannot be achieved while maintaining a growth rate acceptable to integrated circuit (IC) manufacturing. The numerical study also suggests that the high tendency of the precursor for chemical equilibrium on a surface, resulting in nonlinear kinetics by a surface reaction limited process, is crucial to achieve a uniform step coverage as typically observed in SiO2 deposition from tetraethylorthosilicate (TEOS).
Keywords: SILICON DIOXIDE; TETRAETHOXYSILANE; SIMULATION; PRESSURE; FILMS; TETRAETHYLORTHOSILICATE; MECHANISMS; PYROLYSIS; QUALITY; OZONE